Penerapan “One Person One Example” dalam Pembelajaran Ilmu Tajwid sebagai Upaya Menumbuhkan Rasa Cinta Kepada Al-Qur’an - Tri Marfiyanto; Ria Yuliasti Ningsih (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The Qur'an is a collection of the words of Allah SWT which were revealed to the Messenger of Allah SAW through the angel Gabriel which was then taught to mankind. Reading the Qur'an is part of the proof of the faith of Muslims in maintaining and loving the words of Allah, because it is known that the Qur'an has such great and meaningful content in human life and the universe and its knowledge. This community service was carried out at the TPQ Musholla Al-Hikamh Batam which focused on providing an understanding to the TPQ students of the Al-Qur'an class on the science of tajwid, so that the students were allowed in their learning to provide an example of a tajwid reading "One Person One Example" which lasted for 2 months. This service uses the PAR method so that the students are active in participating in this activity. Observations carried out before this activity gave us an idea in an effort to provide an understanding to the students that studying the science of tajwid is not as difficult as previously imagined. The achievement of this activity is to provide a positive impact for the students of the Al-Qur'an class to continue learning to understand the science of Tajwid..